GWC1 is essential for high grain quality in rice. (July 2020) - Guo, Lianan; Chen, Weilan; Tao, Lei; Hu, Binhua; Qu, Guoli; Tu, Bin; Yuan, Hua; Ma, Bingtian; Wang, Yuping; Zhu, Xiaobo; Qin, Peng; Li, Shigui
Highlights: Loss-of-function GWC1 leads to poor grain appearance quality in rice. GWC1 is incorrectly annotated in the reference genome for Nipponbare (MSU). GWC1 encodes an otubain-like protease and highly expresses in early endosperm after fertilization. GWC1 affects starch biosynthesis in rice endosperm. Abstract: Appearance quality is an important determinant of rice quality. Many genes that affect grain appearance quality have been identified, but the regulatory mechanisms that contribute to this trait remain unclear. Here, two grains with chalkiness ( gwc1 ) mutants, gwc1 − 1 and gwc1 − 2, were identified from an EMS-mutagenized population of indica rice cultivar Shuhui498 (R498). The gwc1 mutants had poor grain appearance quality consistent with the measured values for the percentage of grains with chalkiness, square of chalky endosperm, the total starch, amylose and sucrose contents. Milling quality and grain size were also affected in the gwc1 mutants. The gwc1 − 1 and gwc1 − 2 were found to be loss-of-function allelic mutants. GWC1 was mapped to the long arm of rice chromosome 8 using the MutMap strategy and incorrectly annotated in the reference genome for Nipponbare (MSU). The GWC1 gene corresponds to the WTG1/OsOTUB1 gene, which encodes an otubain-like protease with deubiquitinating activity that is homologous to human OTUB1. GWC1 transcripts accumulated to high levels in early endosperm after fertilization and developing inflorescences, and GWC1−green fluorescent protein (GFP) signal was detected in the nucleus and cytoplasm. GWC1 is likely to regulate grain appearance quality through genes involved in sucrose metabolism and starch biosynthesis. Overall, the present findings reveal that GWC1 is important for grain quality and yield due to its effects on grain chalkiness and size.